Batholith recorded mesozoic multistage tectonic evolution of the South china block: A case study of the guandimiao intrusions - Qin, Jin-Hua; Huang, Fan; Wang, Deng-Hong (Frontiers in Earth Science, 2022)
South China is a well-known grand felsic igneous rocks province. However, it is still controversial and not well understood whether the Mesozoic tectono-magmatic pattern is dominated by the subduction of the paleo-Pacific oceanic plate. In this study, we address this question by concentrating on the long-term evolutionary Guandimiao batholith, which has complex lithofacies with different formation ages and can be a superb record of the Mesozoic tectonic evolution in South China. Geochronologically, four stages of magmatism can be identified combined with previous reports: granodiorite (G1, 239 Ma), biotite monzogranite (G2-1) and two-mica monzogranite (G2-2) (230-203 Ma), granite porphyry (G3, 211-190 Ma), and lamprophyre (L4, 121 Ma). G1 and G2-1 have an affinity with I-type granite and were derived from metabasaltic to metatonalitic sources, whereas G2 and G3 show S-type granite characteristics and were derived from the para-metamorphic basement of the Cathaysia block. The L4 was derived from partial melting of garnet and spinel lherzolite and underwent mixing between Mesoproterozoic pelagic and/or terrigenous sediments and the subcontinental lithosphere mantle (SCLM) of South China. The granitoids of the Guandimiao batholith underwent intensely fractional crystallization of feldspar, Ti-bearing minerals, allanite and monazite. The zircon U–Pb dating of L4 in the Guandimiao batholith completely records the six stages of pre-Mesozoic tectonic events in the SCB. During the Mesozoic, the main body of the Guandimiao batholith (G1, G2-1 and G2-2) recorded the closure of the paleo-Tethys Ocean in the Triassic and the subsequent regional extension of the postcollision. G-3 and L4 of the Guandimiao batholith documented the transition of tectonic and dynamic regimes in the early Yanshanian and the rollback and steep subduction of the paleo-Pacific Ocean in the late Yanshanian.